Organizational requisites of successful irrigation system rehabilitation: cases from Nepal - Freeman, David M., author; U.S. Committee on Irrigation and Drainage, publisher (Colorado State University. Libraries, 2000)
This paper describes two irrigation systems in Nepal that have undergone rehabilitation - Sursia-Dudhaura and Bangeri. The experience of farmer-irrigators and their interaction with authorities of the Department of Irrigation is compared and analyzed according to criteria drawn from the literature of common property resource and collective goods theory. The analysis specifies organizational attributes hypothesized to make for successful and sustainable irrigation system rehabilitation, compares the two cases with regard to them, and notes implications. Bangeri is found to have much greater success with its rehabilitation than Sursia-Dudhaura, and the Bangeri irrigation community also possesses the organizational attributes advanced as important to effective local organization whereas Sursia-Dudhaura does not. The operation of local organizations are a most critical part of any canal rehabilitation.
Irrigation and drainage in the new millennium
Not digitized by CSUL Digital Services.
Presented at the 2000 USCID international conference, Challenges facing irrigation and drainage in the new millennium on June 20-24 in Fort Collins, Colorado.